The beneficial effect of a speaker’s gestures on the listener’s memory for action phrases: The pivotal role of the listener’s premotor cortex - Ianì, Francesco; Burin, Dalila; Salatino, Adriana; Pia, Lorenzo; Ricci, Raffaella; Bucciarelli, Monica (Brain and Language, 2018)
•Memory for action sentences improves during observation of congruent gestures.•The listener’s motor system plays a crucial in this enactment effect.•The results reveal a pivotal role of the listener’s premotor cortex. Memory for action phrases improves in the listeners when the speaker accompanies them with gestures compared to when the speaker stays still. Since behavioral studies revealed a pivotal role of the listeners’ motor system, we aimed to disentangle the role of primary motor and premotor cortices. Participants had to recall phrases uttered by a speaker in two conditions: in the gesture condition, the speaker performed gestures congruent with the action; in the no-gesture condition, the speaker stayed still. In Experiment 1, half of the participants underwent inhibitory rTMS over the hand/arm region of the left premotor cortex (PMC) and the other half over the hand/arm region of the left primary motor cortex (M1). The enactment effect disappeared only following rTMS over PMC. In Experiment 2, we detected the usual enactment effect after rTMS over vertex, thereby excluding possible nonspecific rTMS effects. These findings suggest that the information encoded in the premotor cortex is a crucial part of the memory trace.